A collaborative approach to simulation development. (9th June 2017) - Gonzalez, Laura; Allred, Kelly
Abstract : Background: Meeting employer expectations is a challenge for new nurse graduates and their nurse educators. Designing studies to collect specific data on hospital expectations and new nursing graduate deficiencies is needed. Sample: Hospital-based educators and preceptors (n=13) participated in one of two focus groups, to identify problem areas. Senior nursing students (n=64) participated in simulations developed from data obtained in the sessions. Methods: Audio-recorded focus groups were conducted with the goal to identify deficiencies in new graduate nurses. Recordings were transcribed and analysed using thematic analysis. Results: Hospital employer expectation themes identified include attending to basic patient needs, organisational skills, anticipation of risks and consequences, higher order technical skills, communication and ownership/accountability. Two simulations for senior nursing students were developed to address identified deficiencies. Conclusion: Developing meaningful simulations which address deficiencies prior to graduation, in collaboration with potential employers, has the potential to lower the cost of graduate nurse orientation, improve patient outcomes, provide a greater sense of readiness to the graduate nurse and ultimately meet the needs of both the student and employer.